Pendidikan Agama Kristen Gereja dalam Menghadapi Kondisi Psikologi Jemaat Akibat Pandemi Covid-19 - Royke Lantupa Kumowal; Heliyanti Kalintabu (Jurnal Shanan, 2021)
In this article, the author doing a study about the role of christian education in the church in dealing with the psychological conditions of the congregation due to the Covid-19 pandemic. The background for writing this article departs from the information data of printed media, online media which suggests psychological conditions such as stress, excessive pressure and anxiety that arise due to the Covid-19 pandemic outbreak in humans. This article examines the Christian faith in Christian education in the church forum, which plays an important role in dealing with the psychological conditions experienced by the congregation. This article analyzes Christian faith in Christian education in the church forum, analyzes the psychological conditions caused by Covid-19. The purpose of this paper is to provide an understanding of Christian faith which is useful for strengthening the human soul when the person experiences pressure, stress, anxiety, and so on. The method that I use in this article is a qualitative research method. The analytical process used by the author is by analyzing the Bible as the main source and various actual and reliable sources of literature related to the title in this article in order to produce an accountable study.